(untitled) (Laisvalaikio tyrimai, 2020)
Research problem and relevance. With continuously expanding cities, less space is left for public, open areas. The urban planning is performed with regard to urbanistic elements, however, public spaces do not receive enough attention and creative potential (Piekienė, 2015). Individual’s and state’s political concept of public space changes by virtue of the premise of physical rationality and equality, moral values and the role of nature in modern cities. It is now defined as an urban structure, rather than a physical form of space, which meets not just the physiological needs of the individual, but also the general values of the community. The focus is on the moral, social, cultural details and their combination with physiological needs of an individual. Lately, people have become increasingly concerned about their living or recreational environment, necessity and importance of taking care of their health is no longer in doubt. Therefore, M. Burinskienė (2003) notes the aim to create right conditions that meet the interests of different people in various cities. Thus, in order to create sustainable balance between social, economic and environmental aspects, apart from the development of the physical infrastructure of the city, other aspects should be in focus (Čiegis, Žalevičienė, 2012). Analysis of application of public spaces has revealed that there are many scientific articles about the public spaces and related issues, however, opinions, criticism or discussions on this topic go in the same direction – public spaces are considered as isolated objects, rather than one, closely related system. The aim of the research was to assess the circumstances of adapting public spaces to the wellness needs of the local community on the case of Kaunas. The object of the research was the adaptation of public spaces to the needs of the local community. Research methodology. The qualitative research was conducted and a semi-structured interview was selected to collect the data using a convenience sampling method: several interviewees were selected from the researchers’ academic environment (university) upon recommendations. The method based on geographical definition was followed when selecting the interviewees. All interviewees study, work and live in Kaunas. Results. The study revealed that the adaptation and accessibility of public spaces for the wellness needs of the local community was still insufficient. Public spaces were not yet directed to even distribution and adaptability and their formation process did not fully satisfy sustainability criteria. Keywords: public space, leisure, community, wellness, adaption.